2012
DOI: 10.3233/jad-2011-111349
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Aβ1-40, Aβ1-42, Total Tau, and Phosphorylated Tau as Predictors of Dementia in a Cohort of Patients with Mild Cognitive Impairment

Abstract: Mild cognitive impairment (MCI) is a common condition in the elderly which may remain stable along time (MCI-MCI) or evolve into Alzheimer's disease (MCI-AD) or other dementias. Cerebrospinal fluid (CSF) classical biomarkers, i.e., amyloid-β 1-42 (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect the neuropathological changes taking place in AD brains, thus disclosing the disease in its prodromal phase. With the aim to evaluate the power of each biomarker and/or their combination in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 27 publications
6
71
0
3
Order By: Relevance
“…They are also better predictors than clinical variables (MMSE and follow-up time) or genetic variables like the ε4 allele of the APOE gene, confirming previous studies [13,24,25]. The main reason why CSF compound scores are superior is that AD neuropathological changes, especially amyloidosis, may be incidentally present in controls or associated with other pathologies.…”
Section: Discussionsupporting
confidence: 70%
“…They are also better predictors than clinical variables (MMSE and follow-up time) or genetic variables like the ε4 allele of the APOE gene, confirming previous studies [13,24,25]. The main reason why CSF compound scores are superior is that AD neuropathological changes, especially amyloidosis, may be incidentally present in controls or associated with other pathologies.…”
Section: Discussionsupporting
confidence: 70%
“…The decrease rate of p-tau-181 correlated with the MMSE decrease rate in AD subjects''. In line with the latter, Parnetti et al (2012) reinforced the predicting value of CSF biomarkers in identifying converter to AD, by following patients up to 4 years (''81 % of MCI with a low Ab1-42/p-tau ratio progressed to AD'', Parnetti et al 2012).…”
Section: Unmet Needs and Limitationsmentioning
confidence: 83%
“…CSF biomarkers can predict the conversion from MCI to AD (Hansson et al 2006;Mattsson et al 2009;Blom et al 2009). Parnetti et al 2012 recently strengthened this point demonstrating that specific CSF biomarkers (the Ab1-42/ Ab1-40 ratio above all) indeed feature the so-called ''converters'' (AD and MCI-AD as compared to MCI-MCI). Landau et al (2010) concluded that, ''although baseline FDG-PET and episodic memory defaults better predict conversion to AD, p-tau(181p)/Abeta(1-42) ratio maintain its complimentary, but significant role in predicting longitudinal cognitive decline''.…”
mentioning
confidence: 89%
“…Parnetti et al recently developed CSF biomarker models based on logistic regression analysis for the prediction of MCI that evolves into AD dementia within 2 years among individuals with MCI [57]. Using the CSF biomarkers A␤ 1-42 and p-tau for the model development, they obtained a sensitivity of 75% and specificity of 96%.…”
Section: Discussionmentioning
confidence: 99%